(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
232 cases of poisoning admitted to a tertiary care hospital in Pune were studied. As is prevalent, pesticides are commonly involved in poisoning. But a surprising finding was combination of insecticides and medicinal overdose. Cholinesterase estimation is done routinely in all cases of organophosphorous and carbamate compound poisoning but studies are required with regards to utility of cholinesterase estimation in diagnosis and incorrelating severity of poisoning as well as for prognosis.